The Comparison of Multi Representation Based Module and Text Books on Black Principle Material in Physics Learning Reviewed from Student Retention - mirzatullah mir mirzatullah; A Halim; Abdul Hamid (Asian Journal of Science Education, 2020)
Retention was one of internal factors that influenced learning success. The low level of student retention needed tobe a concern of teachers and educational institutions. This study aimed to determine the differences in student retention abilities from the retest results between experimental class who were taught using a multi-representation based module and the control class students who were taught using textbooks on Black principle material. The approach used in this research was a quantitative approach with a quasi-experimental method. Data collection was done by tests using multiple choice questions. Purposive sampling used to select the samples, the sample in this study were 22 students of class XI MIA I as a control class and 22 students of class XI MIA II as an experimental class. Based on the results of data analysis, the retention score of the two classes in an interval of one week was excellent, but the experimental class students achieved higher score than the control class students with a difference of 4.42%. Hypothesis test results obtained tcount (1.71) ttable (1.68), mean reject Ho and accept Ha, which means that the retention score of experimental class students was better than the retention score of control class students.Keyword: Multi representation-based module, textbooks, student retention.